The Analysis of Risk Factors for Mortality in COVID-19 Patients at Sultan Syarif Mohamad Alkadrie General Hospital, Pontianak City - Wia Natasya; Mardjan; Iskandar Arfan (Indonesian Journal of Administration and Health Research (IJAHR), 2025)
RSUD Sultan Syarif Mohamad Alkadrie recorded 308 COVID-19 related deaths in 2021. This study aims to identify risk factors for mortality in COVID-19 patients at the hospital. A quantitative study with a cross-sectional design was conducted with a sample of 2,068 patients treated from January to December 2021 using purposive sampling based on inclusion and exclusion criteria. Data analysis was performed using the chi-square test with a 95% confidence level. The results showed a significant relationship between age (p-value=0.000, PR=3.297), shortness of breath (p-value=0.000, PR=5.559), comorbid diabetes (p-value=0.000, PR=2.800), comorbid hypertension (p-value=0.000, PR=2.507), oxygen saturation (p-value=0.000, PR=5.611), and PCR/swab results (p-value=0.000, PR=3.900) with COVID-19 mortality. Variables that were not significantly associated included gender (p-value=0.807, PR=1.034) and length of stay (p-value=0.235, PR=0.844). Based on these findings, it is recommended that healthcare services focus on early management of mortality risk factors, such as age, comorbidities (diabetes and hypertension), and respiratory symptoms, with proper oxygen monitoring and therapy. Additionally, more attention should be given to elderly patients who are more vulnerable to mortality. Intensive monitoring, use of respiratory support, and appropriate oxygen therapy are essential to reduce COVID-19-related deaths.RSUD Sultan Syarif Mohamad Alkadrie mencatat 308 kematian akibat COVID-19 pada tahun 2021. Penelitian ini bertujuan mengidentifikasi faktor risiko kematian pada pasien COVID-19 di rumah sakit tersebut. Desain penelitian kuantitatif menggunakan pendekatan cross-sectional dengan sampel 2.068 pasien yang dirawat antara Januari hingga Desember 2021 melalui teknik purposive sampling berdasarkan kriteria inklusi dan eksklusi. Analisis data menggunakan uji chi-square dengan tingkat kepercayaan 95%. Hasil penelitian menunjukkan hubungan signifikan antara usia (p-value=0,000, PR=3,297), gejala sesak napas (p-value=0,000, PR=5,559), komorbid diabetes (p-value=0,000, PR=2,800), komorbid hipertensi (p-value=0,000, PR=2,507), saturasi oksigen (p-value=0,000, PR=5,611), dan hasil swab/PCR (p-value=0,000, PR=3,900) dengan kematian pasien COVID-19. Variabel yang tidak berhubungan adalah jenis kelamin (p-value=0,807, PR=1,034) dan lama perawatan (p-value=0,235, PR=0,844). Berdasarkan temuan tersebut, disarankan agar layanan kesehatan lebih fokus pada penanganan dini faktor risiko kematian, seperti usia, penyakit penyerta (diabetes dan hipertensi), dan gejala pernapasan, dengan pemantauan oksigen dan terapi yang tepat. Selain itu, perhatian lebih perlu diberikan kepada pasien lanjut usia yang lebih rentan terhadap kematian. Upaya pemantauan intensif, penggunaan alat bantu pernapasan, dan pemberian terapi oksigen yang sesuai sangat diperlukan untuk mencegah kematian akibat COVID-19.